A motivational model to understand youth sport dropout and enjoyment - Gardner, L. A.; Vella, S. A.; Magee, C. A. (International Journal of Sport Psychology, 2016)
The revised social-cognitive model of achievement motivation (r-SCMAM), additionally incorporating key socials agents, is proposed as an integrative motivational model to explore dropout and associated motivational outcomes, such as enjoyment, in youth sport. Modifications in the r-SCMAM include the use of the 2x2 achievement goal framework and incorporating perceived competence as an independent antecedent of achievement goals. Entity beliefs and performance-avoidance goals are expected to have the most negative associations with enjoyment and increase the likelihood of dropout. Incremental beliefs and mastery-approach goals are expected to have the most positive associations with enjoyment and decrease the likelihood of dropout. Extending on previous theoretical explanations, the proposed model also encompasses social factors and provides hypotheses about how factors will interact and influence outcomes. Social factors to be incorporated in the model include perceptions of relationships with parents, peers, and coaches. Implications for youth sport participation and future research directions are identified.